DOP053 Impact of concomitant immunomodulator use on vedolizumab effectiveness: a multicentre consortium propensity score-matched analysis. (16th January 2018) - Hudesman, D; Chang, S; Shashi, P; Winters, A; Chablaney, S; Meserve, J; Weiss, A; Aniwan, S; Faleck, D; Koliani-Pace, J L; Kochhar, G; Boland, B; et al.
Abstract: Background: We compared the effectiveness of vedolizumab (VDZ) for Crohn's disease (CD) and ulcerative colitis (UC) when used alone vs. in combination with an immunomodulator (IM). Methods: Using a multicentre US-based consortium of Inflammatory Bowel disease (IBD) patients treated with VDZ, we performed propensity score matching for concomitant IM use (1:1) accounting for CD vs. UC, age, sex, prior disease-related hospitalisation within the previous year, disease severity, steroid refractoriness or dependence, prior tumour necrosis factor (TNF)-antagonist failure, number of prior TNF-antagonists used, prior primary nonresponse to TNF-antagonist, and prior thiopurine or methotrexate (MTX) intolerance. Those with prior intolerance to both thiopurine and MTX were excluded. Treatment response was categorised with the Physician Global Assessment (PGA). Using Cox proportional hazard models, we adjusted for type of IM used (thiopurine vs. MTX) and compared cumulative rates of clinical remission (complete resolution of IBD-related symptoms), steroid-free remission (on steroids at baseline, tapered off, no repeat steroid prescription for 4 weeks), and endoscopic healing (absence of ulcers or erosions for CD and Mayo endoscopic subscore of 0 or 1 for UC). Hazard ratios (HRs) and 95% confidence intervals (CIs) are reported for VDZ combination vs. monotherapy. Results: The propensity score model had modest accuracy for predicting treatment status (area under curve 0.68). Of 1087 patients, 718 were included after matching ( n = 450 CD, 47% male, median age 35 years). CD patients treated with VDZ combination therapy had significantly higher cumulative 12-month rates of clinical remission (38% vs. 32%; HR 2.30, 95% CI 1.12–4.74), and numerically but not statistically significant higher 12-month rates of steroid-free remission (31% vs. 17%; HR 2.70, 95% CI 0.78–9.34). Rates of endoscopic healing were comparable (43% vs. 43%; HR 1.18, 95% CI 0.45–2.77). UC patients treated with VDZ combination therapy had significantly higher cumulative 12-month rates of steroid-free remission (47% vs. 30%; HR 4.10, 95% CI 1.06–15.90) and numerically but not statistically significant higher 12-month rates of clinical remission (51% vs. 43%; HR 1.55, 95% CI 0.65–3.70) and endoscopic healing (54% vs. 41%; HR 1.59, 95% CI 0.37–6.70). Conclusions: After accounting for measurable disease and patient-specific characteristics that may impact biologic effectiveness and concomitant IM use, we observed significantly higher rates of clinical remission for CD and steroid-free remission for UC. Randomised controlled trial data are needed to assess the impact of concomitant IM use for VDZ. Statistical analyses conducted at University of California, San Diego. Research funded in part by Takeda.